THE EFFECT OF THE USE OF FINGER PRINT AND PERFORMANCE ALLOWANCE ON EMPLOYEE’S DISCIPLINE IN THE OFFICE OF THE MINISTRY OF RELIGION, PASAMAN DISTRICT - Endarwita, Endarwita; Yurasti, Yurasti; Rahmita, Elchi Rahmita (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine the effect of finger print attendance use and performance allowances on Civil servant (CIVIL SERVANT) discipline in the official representative of the Ministry of Religion, Pasaman Regency. This study employs saturated sampling technique. The method of multiple linear regression analysis used SPSS version 20. The results of the F test showed that Finger Print attendance had a positive and significant role in improving the discipline of civil servant at the Office of the Ministry of Religion, Pasaman Regency. Performance allowances play a positive and significant role in improving the discipline of civil servant at the Office of the Ministry of Religion, Pasaman Regency. Finger print attendance and performance allowances simultaneously play a positive and significant role in increasing civil servant’s discipline at the Office of the Ministry of Religion of Pasaman Regency for 52.9% while the remaining 47.1% is influenced by other variables not examined in this study. Keywords: Fingerprint Attendance, Performance Allowances, and Discipline